Marketing Strategy Through Video Content Platforms: Its Influence On Purchase Intent And Consumer Engagement - Br Sitepu, Natasyah; Andika, Putra; Purba, Nadia Cahya (Jurnal Manajemen, Informatika, Rekayasa Perangkat Lunak dan Teknologi Komunikasi, 2023)
This study aims to explore the influence of marketing strategies through video content platforms on purchase intentions and consumer engagement, with a focus on increasing transparency in marketing practices. Through quantitative and qualitative data analysis, results show that increased transparency in marketing practices, such as clear statements by content creators and the use of fake review detection technology, have a positive impact on consumer trust, purchase intentions, and consumer engagement. However, this study has limitations in that its scope is limited to aspects of transparency, and for future development it is recommended to extend the research to other factors that influence consumer behaviour in the context of marketing through video content platforms.